Development of the ion cyclotron emission diagnostic on the HL-2A tokamak. (1st January 2022) - Tong, R.H.; Fang, K.R.; Yu, X.; Liu, L.Z.; Shi, Z.B.; Yang, Z.C.; Zhong, W.L.; Zhou, Y.; Jiang, M.; Shi, P.W.; Wen, J.; Deng, W.C.; et al.
Abstract: An ion cyclotron emission (ICE) diagnostic, which is based on a B-dot probe, has been recently designed and installed on HL-2A tokamak. The diagnostic is used to study various high-frequency magnetic field fluctuations which can be excited by energetic ions and runaway electrons in the plasma. The ICE diagnostic on HL-2A includes a high-frequency B-dot probe, direct current (DC) block, radio frequency splitters, filter bank and power detectors. The filter bank is composed of 16 channels filters, with the center frequency covering from 10 to 160 MHz, 10 MHz step length and 8 MHz bandwidth. The log detectors with a large dynamic range (from −80 dBm to −20 dBm) are used to detect the bandpass power. Test results of the B-dot probe, filters and power detectors are shown. The signals can also be sampled with a fast analog-to-digital converter with a 14-bit depth, 100 MHz bandwidth and 250 MSample/s sampling rate.